Analysis of transient voltages and currents in short transmission lines on frequency-dependent soils☆ - Pascoalato, T. F.G. [UNESP]; de Araújo, A. R.J.; Kurokawa, S. [UNESP]; Pissolato Filho, J. (Elsevier, 2021)
Accurate modeling of overhead transmission lines (OHTLs) for transient analysis require that the ground which the phase conductors are suspended be considered on the longitudinal impedance and transversal admittance matrices. In this framework, some models deal with the soil as an ideal conductor (constant resistivity ρg and relative permittivity εr). However, it is known fact that real soils are characterized by frequency-dependent (FD) electrical parameters (ρg(f) and εr(f)). Due to these conditions, different formulations to represent the soil with FD parameters have been developed in the last decades. In order to obtain a precise transient response, these models must be incorporated in longitudinal impedance, as the ground-return impedance, and transversal admittance matrices. In this article, an analysis to compute the impact of some FD soil electrical parameters on transient responses is carried out. These responses are calculated for an energization maneuver and ligtning direct strike on OHTLs with different lengths located above constant and FD soil parameter models of low and high soil resistive values. Results show significant differences between the transient responses obtained with the constant and FD soil models, which these variations are more pronounced for soils of high resistivity and for short OHTLs.
Keywords: Electromagnetic transients; frequency-dependent soils; ground-return impedance; transmission lines